Pertahanan Israel:Awal Buramnya Masa Depan Perdamaian di Timur Tengah - Rahman, Abdul (Universitas Muhammadiyah Yogyakarta, 2012)
Even though just established on 1948, the power or Israel Defense cannot be underestimated. The Defense Policy was formed before Israel established. From the Jewish villages or Yishuv, the forming of semi Defense Forces already done. Haganah formation became the main component of Israel Defense Force formation (IDF).After Israel Defense is strong, then the target of IDF formation is to do a political pressure in gaining land. It proved on 1967, Israel success in the occupied Arab countries area which then claimed as their country. From this moment, Israel is doing maneuvers politic to seize Palestine land, then switched to Israel country.